Pengaruh Gaya Kepemimpinan Transformasional, Pelatihan Terhadap Motivasi Kerja Serta Implikasi Kinerja Tenaga Kependidikan Di Universitas Mercu Buana Jakarta - Paijan; Hapsi Ali (Jurnal Ekonomi, 2016)
This study aims to determine the effect of transformational leadership style and training on motivation and its implications on performance both partially and simultaneously. Data collected through survey method and instrument questioner analysis to be distributed to the units of Mercu Buana University academic staff of 126 educators. Research analysis method is descriptive method and quantitative verification tool path analysis (path analysis) was then forwarded to the analysis of determination (R2), partial hypothesis test (t-test) and test hypotheses simultaneously (F test). Prior to the analysis process has been tested instrument with validity and reliability. Results of this study were: 1) the transformational leadership style has no effect on the work motivation of educators in Mercu Buana University; 2) Training effect on the work motivation of educators in Mercu Buana University; 3) transformational leadership style and training of education personnel motivation to work directly and indirectly in Mercu Buana University; 4) transformational leadership style of the performance of educators at Mercu Buana University; 5) Training of educational personnel in the performance of Mercu Buana University; 6) transformational leadership style and training of education personnel performance both directly and indirectly in Mercu Buana University; 7) To analyze the effect of motivation on the performance of work at the University of Mercu Buana.